MicroRNA-21-5p profile in the alveolar bone following tooth extraction in medication-related osteonecrosis of the jaw rat model - Morakotsriwan, Manta; Chanamuangkon, Theerapat; Vacharaksa, Anjalee; Limlawan, Pirawish (Frontiers in Dental Medicine, 2024)
ObjectiveThis study aimed to compare microRNA-21-5p expressions at the extraction wound in the maxillary bones of rats with medication-related osteonecrosis of the jaw (MRONJ) and normal rats at different time points.Materials and methodsIn total, 18 female, 8-week-old Sprague-Dawley rats were randomly assigned to the experimental group (n = 9) and the control group (n = 9). To establish MRONJ in the right maxillary first molar area in the experimental group, zoledronate (66 µg/kg) and dexamethasone (5 mg/kg) were administered intraperitoneally every other day for 2 weeks before tooth extraction. Normal saline was administered in the control group. After tooth extraction, the drugs were continuously administered until the experimental endpoints, namely 1, 14, and 28 days post-tooth extraction. At each endpoint, three rats from each group were euthanized. The maxilla bones at the wound area were harvested. A real-time polymerase chain reaction (RT-PCR) was performed to compare the expression levels of miRNA-21-5p at each time point between the MRONJ group and the control group.ResultsFrom their gross appearance, the rats that received zoledronate and dexamethasone developed MRONJ as demonstrated by non-healing wounds and exposed bone at 14 and 28 days post-extraction in contrast to the controls. The RT-PCR showed that the expression levels of miRNA-21-5p were relatively higher in the MRONJ rats compared to the control rats at day 14 and then the difference was lower at day 28 post-tooth extraction.ConclusionThe findings indicated that the microRNA-21-5p expression levels varied during the socket healing process in the MRONJ rats, reaching a peak at 2 weeks after tooth extraction.